PENDIDIKAN AGAMA KATOLIK UNTUK GENERASI Z: STRATEGI DAN TANTANGAN DI ERA DIGITAL - Kurnia Saputra, Yohanes Chandra (Lembaga Penelitian STKIP Widya Yuwana, 2025)
Generation Z faces a number of challenges related to their Catholic faith amidst the dynamics of modernity and technological developments. The problem faced is the lack of active involvement in traditional religious practices. Generation Z is also faced with the challenge of understanding and identifying with their own Catholic beliefs. In the midst of advances in information and cultural plurality, generation Z is often exposed to various views and values ​​that conflict with the teachings of the Catholic religion. The aim of this research is to provide a descriptive analysis regarding the contextual implementation of Catholic religious education in the era of various challenges faced by generation Z. The implementation of Catholic Religious Education in the era of generation Z needs to be adapted to the unique dynamics and characteristics of generation Z. The relevant approach that can be applied is integrating technology and digital media into learning. A collaborative and participatory learning approach will be more effective in reaching generation Z. Teachers can encourage open discussion and reflection on Catholic religious concepts, as well as encourage students to share their own views and experiences. Catholic religious educators need to emphasize the relevance and applicability of Catholic religious teachings in everyday life.